Dynamic Response of Pre-Stressed Spatially Curved Thin-Walled Beams of Open Profile - Rossikhin, Yury A.; Shitikova, Marina V.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This short book analyses the dynamic stability with respect to small perturbations, as well as the local damage of geometrically nonlinear elastic, spatially curved, open section beams with axial precompression. Transient waves, which are the surfaces of strong discontinuity and wherein the stress and strain fields experience discontinuities, are used as small perturbations; in so doing the discontinuities are considered to be of small magnitude. Such waves are initiated during low-velocity impacts upon thin-walled beams. The theory of discontinuities and the method of ray expansions which allow one to find the desired fields behind the fronts of the transient waves in terms of discontinuities in time-derivatives of the values to be found, are used as the methods of solution for short-time dynamic processes. The example of using the ray expansions for analyzing the impact response of spatially curved thin-walled beams of open profile is demonstrated by solving the problem about the normal impact of an elastic hemispherical-nosed rod upon an elastic arch representing itself a channel-beam curved along an arc of the circumference. The influence of the initial stresses on the dynamic fields has been investigated.
Introduction -- Problem Formulation and Governing Equations -- Impact Response of a Thin-walled Beam of Open Profile -- Conclusion -- Appendix.
Keywords: Engineering; Computer science; Mechanics; Materials; Civil engineering; Engineering; Continuum Mechanics and Mechanics of Materials; Computational Science and Engineering; Mechanics; Civil Engineering